Performance Analysis of Radiation Detection Devices in Elevated Natural Radiation Zones: A Case Study of Mamuju Regency, West Sulawesi Indonesia - Abdullah, Adi Rahmansyah Amir; Permana, Sidik; Srigutomo, Wahyu; Maulana, Alan; Seno, Haryo; Purnama, Dikdik Sidik; Tursinah, Rasito; Humolungo, Ismail; Zulfahmi, Zulfahmi (Journal of Engineering and Technological Sciences, 2025)
Three radiation detection tools were employed to assess natural radiation levels in Mamuju Regency, West Sulawesi, Indonesia. These tools comprised the NaI(Tl) Scintillator, the Geiger Muller Counter (GMC), and the Electronic Personal Dosimeter (EPD). The NaI(Tl) Scintillator and GMC measured ambient dose equivalent (H*(10)), while the EPD exclusively gauged personal dose equivalent (Hp(10)). A total of 75 measuring points were designated for assessment. Results from H*(10) measurements indicated that the GMC recorded an average H*(10) 41% higher than that of the NaI(Tl) Scintillator, with specific rates of 0.769 µSv/h and 0.457 µSv/h, respectively. Both instruments exhibited proficiency in detecting elevated levels of radiation. Discrepancies in the outcomes were attributed to differences in detector type and efficiency. The GMC, equipped with an energy-compensated detector, demonstrated enhanced efficiency compared to the NaI(Tl) Scintillator, particularly when subjected to high energy flux radiation. Anomalies emerged in the Hp(10) measurements, which surpassed the H*(10) measurements. This difference is due to the EPD's use of a conventional GM detector, which is capable of detecting gamma, beta, and X-ray radiation